Diverse Evolutionary Origins and Mechanisms of Lens Regeneration - Henry, Jonathan J (Mol Biol Evol, 2018)
In this review, we compare and contrast the three different forms of vertebrate lens regeneration: Wolffian lens regeneration, cornea-lens regeneration, and lens regeneration from lens epithelial cells. An examination of the diverse cellular origins of these lenses, their unique phylogenetic distribution, and the underlying molecular mechanisms, suggests that these different forms of lens regeneration evolved independently and utilize neither conserved nor convergent mechanisms to regulate these processes.